A nuclear phylogenetic analysis: SNPs, indels and SSRs deliver new insights into the relationships in the 'true citrus fruit trees' group (Citrinae, Rutaceae) and the origin of cultivated species - García-Lor, Andrés; Curk, Franck; Snoussi-Trifa, Hager; Morillon, Raphael; Ancillo, Gema; Luro, Francois; Navarro, Luis; Ollitrault, Patrick (2017)
Background and Aims: Despite differences in morphology, the genera representing ‘true citrus fruit trees’ are sexually compatible, and their phylogenetic relationships remain unclear. Most of the important commercial ‘species’ of Citrus are believed to be of interspecific origin. By studying polymorphisms of 27 nuclear genes, the average molecular differentiation between species was estimated and some phylogenetic relationships between ‘true citrus fruit trees’ were clarified.